Ice templating of ZrB2–SiC systems. Issue 8 (September 2015) - Medri, Valentina; Sciti, Diletta; Dalle Fabbriche, Daniele; Piancastelli, Andreana; Landi, Elena
Abstract: Ice templating of a binary ZrB2 –SiC system was set to obtain porous architectures with lamellar structure. Two commercial ammonium poly-acrylates, with different molecular weights and pH range of activity, were used as dispersants. Slurries were produced by varying solid loadings (38–48 vol%) and/or the dispersant concentrations (from 0.4 to 2 wt%). It was found that an excess of dispersant is necessary to achieve a lamellar morphology. The more effective is the dispersant in optimizing electro-steric repulsions between particles, the more effective is in promoting the formation of a lamellar morphology. Preliminary compressive strength tests were carried out.